Sedimentological and deformational criteria for discriminating subglaciofluvial deposits from subaqueous ice‐contact fan deposits: A Pleistocene example (Ireland). Issue 5 (27th March 2014) - Ravier, Edouard; Buoncristiani, Jean‐François; Clerc, Sylvain; Guiraud, Michel; Menzies, John; Portier, Eric; Eyles, Nick
Abstract A pit located near Ballyhorsey, 28 km south of Dublin (eastern Ireland), displays subglacially deposited glaciofluvial sediments passing upwards into proglacial subaqueous ice‐contact fan deposits. The coexistence of these two different depositional environments at the same location will help with differentiation between two very similar and easily confused glacial lithofacies. The lowermost sediments show aggrading subglacial deposits indicating a constrained accommodation space, mainly controlled by the position of an overlying ice roof during ice‐bed decoupling. These sediments are characterized by vertically stacked tills with large lenses of tabular to channelized sorted sediments. The sorted sediments consist of fine‐grained laminated facies, cross‐laminated sand and channelized gravels, and are interpreted as subglaciofluvial sediments deposited within a subglacial de‐coupled space. The subglaciofluvial sequence is characterized by glaciotectonic deformation structures within discrete beds, triggered by fluid overpressure and shear stress during episodes of ice/bed recoupling (clastic dykes and folds). The upper deposits correspond to the deposition of successive hyperpycnal flows in a proximal proglacial lake, forming a thick sedimentary wedge erosively overlying the subglacial deposits. Gravel facies and large‐scale trough bedding sand are observed within this proximal wedge, while normally graded sand beds with developed bedforms are observed further downflow. The building of the prograding ice‐contact subaqueous fan implies an unrestricted accommodation space and is associated with deformation structures related to gravity destabilization during fan spreading (normal faults). This study facilitates the recognition of subglacial/submarginal depositional environments formed, in part, during localized ice/bed coupling episodes in the sedimentary record. The sedimentary sequence exposed in Ballyhorsey permits characterization of the temporal framework of meltwater production during deglaciation, the impact on the subglacial drainage system and the consequences on the Irish Sea Ice Stream flow mechanisms.